Perspectives Historical and Contemporary on Employee Turnover: A Literature Review - dos Santos Fortunato, Wellington; Doria Calvosa, Marcello Vinicius (Cuadernos de Administración, 2024)
For over a century, employee turnover has been a topic of interest for many researchers globally. This literature review primarily aimed to examine the evolution of employee turnover from the perspective of senior researchers and to discuss potential future research directions in the field. The methodology was qualitative, involving a comprehensive bibliographic review. Searches were conducted in databases such as Scopus, SciELO, PsycArticles, JSTOR, Wiley, ScienceDirect, and Google Scholar, resulting in the analysis of 77 articles from international journals ranked “Q1” in the Scimago Journal & Country Rank (2022 evaluation) and Brazilian journals from the “A” stratum of Qualis/CAPES (2017-2020 quadrennium). The key findings revealed that: (i) the historical evolution of turnover studies highlights the increasing interest in the topic and the pursuit of understanding its causes, characteristics, and consequences; (ii) initially, the phenomenon was addressed through individual characteristics and aspects, but research has evolved towards collective approaches at group, unit, and organizational levels; (iii) the studies analyzed in recent decades highlight the diversity of contexts across different continents, with a focus on cultural and value influences affecting turnover. The main conclusions indicate that, historically, the phenomenon of employee turnover began to be analyzed in the USA in the early 1900s, later evolving with the application of various theories, and contemporary research focuses on approaches that consider organizational and socio-cultural influences.